SMART GARDEN SEBAGAI IMPLEMENTASI SISTEM KONTROL DAN MONITORING TANAMAN BERBASIS TEKNOLOGI CERDAS - I.W.B. Darmawan; I.N.S. Kumara; D.C. Khrisne (Program Studi Teknik Elektro UNUD, 2021)
Smart garden is a control system application to monitor watering/plant care that utilizesintelligent technology. This study reviews the components used in smart gardens and theapplication of smart gardens in community life. The components commonly used in smartgarden such as BLYNK App, Antares, wireless sensor and actuators networks, SMS Gateway,capacitive soil moisture sensor, temperature sensor, light sensor, Arduino nano, Arduino unoR3, Arduino mega 2560, and Raspberry Pi. Smart garden has been applied in agriculture andfarm with the aim of monitoring plant growth, optimizing harvest activities, developingecotourism and Adiwiyata program.